Annexin A1 peptide is able to induce an anti-parasitic effect in human placental explants infected by Toxoplasma gondii - de Oliveira Cardoso, Marystela Fávero; Moreli, Jusciele Brogin; Gomes, Angélica Oliveira; de Freitas Zanon, Caroline [UNESP]; Silva, Ana Elizabete [UNESP]; Paulesu, Luana Ricci; Ietta, Francesca; Mineo, José Roberto; Ferro, Eloísa Amália; Oliani, Sonia Maria [UNESP] (Elsevier, 2018)
This study was conducted to investigate annexin A1 (ANXA1) functions in human placental explants infected with Toxoplasma gondii (T. gondii). We examined the first and third trimester placental explants infected with T. gondii (n = 7 placentas/group) to identify the number and location of parasites, ANXA1 protein, potential involvement of formyl peptide receptors (FPR1 and FPR2), and COX-2 expressions by immunohistochemistry. Treatments with Ac2-26 mimetic peptide of ANXA1 were performed to verify the parasitism rate (β-galactosidase assay), prostaglandin E2 levels (ELISA assay), and ANXA1, FPR1 and COX-2 expression in third trimester placentas. Placental explants of third trimester expressed less ANXA1 and were more permissive to T. gondii infection than first trimester placentas that expressed more ANXA1. Ac2-26 treatment increases endogenous ANXA1 and decreases parasitism rate, COX-2, and prostaglandin E2 levels. Altogether, these data provide further insight into the anti-parasitic and anti-inflammatory effects of ANXA1 in placentas infected with T. gondii.
Keywords: Ac2-26 peptide; Annexin A1; Placenta; Toxoplasmosis